Organic Agriculture in Least Developed Countries in Relation to the Development of the Organic Farming Sector in Poland. The Example of African Countries versus the Organic Sector in Poland - Anna Rydz‑Zḃikowska (Comparative Economic Research. Central and Eastern Europe, 2020)
Over the past few years, organic farming has seen a dynamic development globally. In 2015, the global market for organic products was exteuro81.6 billion, rising to more than exteuro90 billion in 2018 (Sẃiatowy rynek produktoẃ ekologicznych osiagnał wartosć\' 90 mld euro 2019). There has also been a significant rise in the production of organic products by the group of Least Developed countries (LDCs) (such as African countries), which are being supported by all the World Trade Organisation negotiations within the Doha Round. The aim of this article is to present different definitions of organic farming according to the most important international organizations. Furthermore, it will examine the status of the organic farming sector in selected examples of Africa's LDCs and investigate the results of Doha's negotiations within the agricultural market (particularly towards LDCs). Finally, it will investigate the status and the latest developments of organic farming in the LDCs compared to Poland. The research methods used in the article include an analysis of available documentary and literary sources on the topics in question, the development of relevant statistical surveys, and the deductive approach to draw conclusions from the development of organic agriculture in LDCs and Poland (as an example of a Central European Country). – – W ciagu ostatnich kilku lat obserwuje sie dynamiczny rozwoj́ rolnictwa ekologicznego. Globalny obszar rolnictwa ekologicznego stale rosńie. Co wiecej, rynek organiczny rozwija sie nie tylko w Europie, ale takzė w Ameryce Poĺnocnej, a takzė w innych czesćiach sẃiata. Rynek produktoẃ ekologicznych stale rosńie i nalezẏ podkresĺic\', zė w 2015 r. sẃiatowy rynek produktoẃ ekologicznych wzrośł do 81,6 mld euro, przekraczajac wartosć\' 90 mld euro w 2018 r. Znaczaco wzrosła roẃniezṗrodukcja produktoẃ ekologicznych , wytwarzanych przez grupe krajoẃ najsłabiej rozwinietych (takich jak wybrane kraje afrykanśkie), ktoŕe sa wspierane przez postanowienia wynikajace z negocjacji Sẃiatowej Organizacji Handlu w ramach Rundy z Doha. Celem tego artykułu jest przedstawienie roźṅych definicji rolnictwa ekologicznego według najwazṅiejszych organizacji miedzynarodowych. Ponadto kluczowe bedzie zbadanie obecnego statusu sektora rolnictwa ekologicznego w wybranych przykładach krajoẃ najsłabiej rozwinietych w Afryce oraz okresĺenie wynikoẃ negocjacji z Doha na rynku rolnym (szczegoĺnie w odniesieniu do krajoẃ najsłabiej rozwinietych). Wreszcie nalezẏ przyjrzecśie problemowi, jaki jest stan i jakie sa najnowsze osiagniecia rolnictwa ekologicznego w odniesieniu do krajoẃ najsłabiej rozwinietych w poroẃnaniu z Polska. Metody badawcze zastosowane w artykule obejmuja analize dostepnych zŕod́eł dokumentalnych i literackich dotyczacych omawianych zagadnien\', opracowanie odpowiednich badanśtatystycznych oraz zastosowanie podejsćia dedukcyjnego w celu wyciagniecia wnioskoẃ ze statusu rozwoju rolnictwa ekologicznego w krajach najmniej rozwinietych i Polski (jako przykładu kraju Europy Sŕodkowej).
Keywords: O13; O18; O53; O55; P45; P48; Q01; Q13; Q17; Q18; Q56; 330; organic agriculture; organic products; sustainable development; least developed countries; World Trade Organisation; Doha Round